SIMA and SBIS Effect on Liquidity in Sharia Commercial Banks - Rahmat, Ali; Rizal, Sofyan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The study aims to determine the effect of the Interbank Mudharabah Investment Certificate (SIMA) on Liquidity in Islamic Commercial Banks, also to determine the effect of the Bank Indonesia Sharia Certificate (SBIS) on Liquidity in Islamic Commercial Banks, and determine the effect of SIMA and SBIS on Liquidity in Islamic Commercial Banks simultaneously. The type of research used in this research is quantitative research. Quantitative research is one of the research methods used to test a theory, present a fact or describe statistics, show relationships between variables, and some are to develop concepts, develop understanding, or describe many things. This study uses a quantitative approach in the form of financial ratios based on time series. Time series is data arranged chronologically according to time on a particular variable. The data used is monthly data. SIMA has no effect on liquidity in Islamic Commercial Banks for the 2016-2019 period, and SBIS has no effect on liquidity in Islamic Commercial Banks for the 2016-2019 period. At last, SIMA and SBIS have no simultaneous effect on liquidity in Islamic Commercial Banks for the 2016-2019 period.